Stress concentration of endodontically treated molars restored with transfixed glass fiber post: 3d-finite element analysis - Souto Borges, Alexandre Luiz [UNESP]; Vieira Grangeiro, Manassés Tercio [UNESP]; De Andrade, Guilherme Schmitt [UNESP]; De Melo, Renata Marques [UNESP]; Baroudi, Kusai; Silva-Concilio, Laís Regiane; Mendes Tribst, João Paulo (MDPI, 2021)
The loss of dental structure caused by endodontic treatment is responsible for a decrease in tooth resistance, which increases susceptibility to fracture. Therefore, it is important that minimally invasive treatments be performed to preserve the dental structure and increase the resistance to fracture of endodontically treated posterior teeth. To evaluate under axial loads, using the finite element method, the stress distribution in endodontically treated molars restored with both transfixed or vertical glass fiber posts (GFP) and resin composite. An endodontically treated molar 3D-model was analyzed using finite element analyses under four different conditions, class II resin composite (G1, control model), vertical glass fiber post (G2), transfixed glass fiber posts (G3) and vertical and transfixed glass fiber posts (G4). Ideal contacts were considered between restoration/resin composite and resin composite/tooth. An axial load (300 N) was applied to the occlusal surface. The resulting tensile stresses were calculated for the enamel and dentin tissue from five different viewports (occlusal, buccal, palatal, mesial and distal views). According to the stress maps, similar stress trends were observed, regardless of the glass fiber post treatment. In addition, for the G1 model (without GFP), a high-stress magnitude can be noticed in the proximal faces of enamel (7.7 to 14 MPa) and dentin (2.1 to 3.3 MPa) tissue. The use of transfixed glass fiber post is not indicated to reduce the stresses, under axial loads, in both enamel and dentin tissue in endodontically treated molar with a class II cavity.
Keywords: Dental materials; Dental restoration failure; Endodontically treated teeth; Finite element analysis